2014
DOI: 10.1080/10255842.2014.974580
|View full text |Cite
|
Sign up to set email alerts
|

Reasons why dynamic compression plates are inferior to locking plates in osteoporotic bone: a finite element explanation

Abstract: While locking plate fixation is becoming increasingly popular for complex and osteoporotic fractures, for many indications compression plating remains the standard choice. This study compares the mechanical behaviour of the more recent locking compression plate (LCP) device, with the traditional dynamic compression plates (DCPs) in bone of varying quality using finite element modelling. The bone properties considered include orthotropy, inhomogeneity, cortical thinning and periosteal apposition associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 45 publications
(73 reference statements)
1
52
0
Order By: Relevance
“…This indicates that LCP is superior at resisting axial loading and bending moments and DCP is superior at resisting torsional loading of unstable fractures. LCP has been reported to be more secure in fixing unstable and osteoporotic fractures due to its angle stability . However, no conclusive discovery could be made on the fixation stability of LCP and DCP in terms of resisting different forces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that LCP is superior at resisting axial loading and bending moments and DCP is superior at resisting torsional loading of unstable fractures. LCP has been reported to be more secure in fixing unstable and osteoporotic fractures due to its angle stability . However, no conclusive discovery could be made on the fixation stability of LCP and DCP in terms of resisting different forces.…”
Section: Discussionmentioning
confidence: 99%
“…Two idealized identical diaphyseal tibias with a length of 49.0 mm were created to represent the two long bone fracture fragments . The geometric characteristics for the bone were selected to match reported values of cortical thickness and cross‐sectional areas for healthy young adults, which are 5.1 mm and 319.2 mm 2 , respectively .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, studies have also shown that the pull-out strength of conventional screws increases with bone density [16,17] which can result in equivalent or even better results than locked plating in healthy bone [14]. These differences arise due to two main factors: (1) The preloads involved in compression screw tightening increase strain levels at the screw-bone interface even before physiological loads are applied, whereas locking screws have negligible screw-tightening preload and resulting strains [13,18]; and (2) During physiological loading, compression plating allows for frictional load transfer at the plate-bone interface; locked plating, on the other hand, transfers all physiological loads via the screw-bone interface [18]. In particular, the localised high tensile strains produced by conventional screws have been shown to be responsible for their poorer performance in osteoporotic bone [18].…”
Section: Introductionmentioning
confidence: 99%